PENGARUH KUALITAS LAYANAN, BRAND IMAGE, HARGA DAN KEPERCAYAAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN (Studi layanan E-commerce Berrybenka.com) - Adyanto, Brian Cahyo; Santosa, Suryono Budi (Diponegoro Journal of Management, 2018)
This study aims to analyze the influence of Service Quality, Brand Image, Price and Product Trust on purchasing decisions on  Berrybenka.com e-commerce platform. These days, E-Commerce has became common thing in community, technological developments and facilities advances make this platform has growing demand in all market segments. From the start of its ease to the speed of E-commerce services into the spotlight of consumers. Quality of Service, Brand Image, Price and Products Trust are widely used as reference consumers in determines purchasing decisions, especially in the city of Semarang that is high sensitivity to a product. So in this study, want to discover how or what matters affect the Purchase Decision from consumers in the world of E-Commerce. In this study data were collected from 140 selected respondents who had made purchases on Berrybenka.com E-commerce platform. Analysis method with  AMOS program.  The results show that  Quality of Service,  Brand Image, Price has a positive and significant effect on Product Trust. Then, Product Confidence has a positive and significant effect on Purchase Decision.